Stridor in an Elderly Woman: An Unusual Presentation of a Giant Thyroglossal Cyst - Sithananda Kumar Venkatesan; Kiruba Shankar Manoharan; Pradipta Kumar Parida; Arun Alexander; S. Gopalakrishnan (Case Reports in Otolaryngology)
Thyroglossal cysts are one of the most common midline neck masses. They usually present as midline painless cystic neck mass in the first three decades of life. These anomalies are very rare in elderly patients and may pose difficult diagnostic and therapeutic challenges. Here, we report a case of giant thyroglossal cyst in a 72-year-female patient who presented with stridor, hoarseness of voice, and vocal cord paresis with gross distortion of normal airway anatomy secondary to pressure effect of the mass. The gross distortion and displacement of airway along with respiratory distress in this patient posed a difficult situation in securing the airway. The airway was secured by a unique way of orotracheal intubation with the help of a ventilating airway exchange catheter. The cyst was excised in toto under general anaesthesia. The stridor completely resolved after surgery and tracheostomy was avoided.